Application of Bentonite-Based Sediment Capping for Eutrophication Control: A Case Study of Lake Batur, Bali - Annisa Rehan Fadhila; Irhamni; Astried Sunaryani (Jurnal Serambi Engineering, 2026)
Increasing nutrient inputs, particularly phosphate and nitrogen, have contributed to eutrophication in Lake Batur and increased the risk of water quality degradation. This study evaluated the effectiveness of sediment capping using activated and non-activated bentonite for nutrient removal, including total phosphorus (TP), total nitrogen (TN), nitrate, and ammonia. Characterization using SEM-EDX and FTIR showed that the activation process altered the surface morphology and chemical properties of bentonite, resulting in a more open structure and higher silicon and aluminum contents. Shifts in the absorption bands of –OH, Si–OH, and Si–O–Si groups indicated surface modification without damaging the montmorillonite framework. The results demonstrated that non-activated bentonite achieved the highest removal efficiency for total phosphorus, reaching 87%. Activated bentonite showed better performance in reducing total nitrogen and nitrate, with removal efficiencies of 61% and 79%, respectively. Meanwhile, nitrate removal by non-activated bentonite reached 78%. Ammonia removal remained relatively limited, where activated bentonite reduced ammonia concentration by 30%, while non-activated bentonite showed a slight increase in ammonia concentration of −12%. Overall, both activated and non-activated bentonite exhibited potential as sediment capping materials for controlling nutrient release in aquatic systems.